2018
DOI: 10.1136/heartjnl-2018-313922
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of pericardial diseases in Africa: a systematic scoping review

Abstract: ObjectivesThis scoping review sought to summarise available data on the prevalence, aetiology, diagnosis, treatment and outcome of pericardial disease in Africa.MethodsWe searched PubMed, Scopus and African Journals Online from 1 January 1967 to 30 July 2017 to identify all studies published on the prevalence, aetiologies, diagnosis, treatment and outcomes of pericardial diseases in adults residing in Africa.Results36 studies were included. The prevalence of pericardial diseases varies widely according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
0
43
0
4
Order By: Relevance
“…In SSA, the most common cause of pericarditis is tuberculosis accounting for about 65-91% of cases of pericardial disease across studies [88][89][90], compared to HIC of western world where about 80% or more of pericardial effusions are idiopathic with tuberculosis accounting for only <5% of cases [91,92]. In a recent systematic review that included 36 studies from SSA, tuberculosis was the most frequent cause of pericardial diseases in both HIV-uninfected and HIV-infected populations, followed by malignancies and rheumatological diseases [88].…”
Section: Pericarditismentioning
confidence: 99%
“…In SSA, the most common cause of pericarditis is tuberculosis accounting for about 65-91% of cases of pericardial disease across studies [88][89][90], compared to HIC of western world where about 80% or more of pericardial effusions are idiopathic with tuberculosis accounting for only <5% of cases [91,92]. In a recent systematic review that included 36 studies from SSA, tuberculosis was the most frequent cause of pericardial diseases in both HIV-uninfected and HIV-infected populations, followed by malignancies and rheumatological diseases [88].…”
Section: Pericarditismentioning
confidence: 99%
“…Cardiovascular diseases are the second commonest cause of premature disability and death in sub-Sahara Africa (SSA) [4][5][6]. A greater bulk of the burden of heart disease, kidney failure, stroke and premature death in this region is accounted for by hypertension [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Despite he was started on isoniazid, rifampin, ethambutol, and pyrazinamide plus B6, he showed improvement but fever continued few more days, moxifloxacin was added and fever resolved. An extensive review on the causes of pericarditis conducted by Noubiap JJ, et al revealed that M. tuberculosisis a responsible agent in pericarditis, but not hemorrhagic pericarditis, and furthermore, no unique 2D-echocardiographic signs were detected [9]. A cross-sectional study from Sudan between January 2011 and June 2012 enrolled 985 patients, 22.7% (224) were extrapulmonary tuberculosis, only 1.9% [4] patients were pericardial, and none were hemorrhagic [10].…”
Section: Discussionmentioning
confidence: 99%